Examining the relationship between yo-yo intermittent rest test results and performance in football players - Karabulak, A.; Özcan, S. (Turkish Journal of Sport and Exercise, 2024)
The purpose of your study; The aim is to determine the relationship between aerobic endurance and the performance of football players. 30 licensed football players (age 18,33±0,47 years, height 179,5±10,6 cm, body weight 76,6±11,5 kg) playing in the Turkish Football Federation U-19 Development League voluntarily participated in the research. Football players' Yo-Yo IRT1 test was measured twice at eight-week intervals on an artificial football field. During the test, Heart rate (HR) (beats/min) and afterwards Maximal Aerobic Power (VO2max) values were measured and calculated. Paried T-test, one of the parametric tests, was used to determine whether there was a difference in terms of Yo-Yo IRT 1 test, VO2max values and pulse values. All analyzes were processed at the 0.05 significance level. In conclusion; There is no statistically significant difference p>0.005 between the first and last values of the distances traveled by the football players who were subjected to the Yo-Yo IR1 test first and last measurement test, their HR and their measured VO2max values.